2016
DOI: 10.3390/rs8100847
|View full text |Cite|
|
Sign up to set email alerts
|

Using Ordinary Digital Cameras in Place of Near-Infrared Sensors to Derive Vegetation Indices for Phenology Studies of High Arctic Vegetation

Abstract: Abstract:To remotely monitor vegetation at temporal and spatial resolutions unobtainable with satellite-based systems, near remote sensing systems must be employed. To this extent we used Normalized Difference Vegetation Index NDVI sensors and normal digital cameras to monitor the greenness of six different but common and widespread High Arctic plant species/groups (graminoid/Salix polaris; Cassiope tetragona; Luzula spp.; Dryas octopetala/S. polaris; C. tetragona/D. octopetala; graminoid/bryophyte) during an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 63 publications
(94 reference statements)
6
50
0
Order By: Relevance
“…For NDFI NIR-G , NDVI 1 , and NDVI 2 , all calculated from NIR, the R 2 of combinations (NDFI NIR-G and NDVI 1 ) and (NDFI NIR-G and NDVI 2 ) were higher than 0.87 for both combinations. Anderson et al (2016) [38] also found that the vegetation indices from active sensors had high correlations. They reported that the vegetation indices measured from active and passive sensors were correlated (R 2 > 0.70) for the same plant species.…”
Section: Discussionmentioning
confidence: 97%
“…For NDFI NIR-G , NDVI 1 , and NDVI 2 , all calculated from NIR, the R 2 of combinations (NDFI NIR-G and NDVI 1 ) and (NDFI NIR-G and NDVI 2 ) were higher than 0.87 for both combinations. Anderson et al (2016) [38] also found that the vegetation indices from active sensors had high correlations. They reported that the vegetation indices measured from active and passive sensors were correlated (R 2 > 0.70) for the same plant species.…”
Section: Discussionmentioning
confidence: 97%
“…To complement the use of airborne and satellite imagery to measure vegetation pigments and classify biophysical properties in Arctic ecosystems, the use of true‐color digital photography and red, green, and blue (RGB) indices to infer photosynthetic activity and foliar condition is a promising area of study and should be examined (Anderson et al. , Beamish et al. ).…”
Section: Introductionmentioning
confidence: 99%
“…, Anderson et al. ), as well as containing a sensitivity to changes in plant photosynthetic pigments (Ide and Oguma ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This damage was shown to be caused by stressful conditions during winter [6]. Usually, lower NDVI values (<0.6) are measured for species and sites operating within more adverse environmental conditions, while species and sites in good health had a NDVI of 0.6-0.7 with species and sites in very good condition having NDVI values > 0.7 [6,52]. Red edge modification of SR.…”
Section: Calculation Of Vegetation Indicesmentioning
confidence: 99%